Diversified and intensified rice-based cropping systems in the southern coastal zone of Bangladesh - CGIAR Research Program on Rice (2020)
Testing of various cropping systems in field experiments completed: a study conducted for three years (2016–2019) in Polder 30 that included five cropping systems [improved varieties of rice-maize (R-M); rice-mungbean (R-MB); rice-sunflower (R-S); traditional varieties of rice-mungbean (RTrad-MBTrad); and rice-fallow (RTrad-F)].